Black Pulp : Genre Fiction in the Shadow of Jim Crow - Hefner, Brooks E. (Book collections on Project MUSE., 2021)
"A deep dive into mid-century African American newspapers, exploring how Black pulp fiction reassembled genre formulas in the service of racial justice"--